HUBUNGAN KEAKTIFAN MAHASISWA DALAM BERORGANISASI DENGAN KEMAMPUAN PUBLIC SPEAKING PADA MAHASISWA FISIP UNIVERSITAS SRIWIJAYA - Ria agustina (Jurnal Media Sosiologi (JMS), 2021)
The purpose of this study was to determine the relationship between student activity in organizing with public speaking skills in the students of the faculties of social science and political science at sriwijaya university. The hypothesis in this study there is a relationship between student activity in organizing with public speaking skills in the students of the faculties of social science and political science at sriwijaya university. The sample of the study was the students of the faculty of social sciences and political sciences in the class of 2016,2017, and 2018 as many as 94 people taken through the solvin method. The results of the study used pearson product moment correlation analysis. The analysis results obtained a significance value of 0,000(p<0,05) which indicates that there is a significant relationsip between student activity in organizing with public speaking skills in the students. Correlation value obtained at 0,983 indicates a positive. Thus the hyphotesis proposed in the study was accepted